Pengaruh Kompetensi, dan Servant Leadership serta Disiplin Kerja terhadap Kinerja Pegawai Perusahaan Listrik Negara (PLN) Persero Kota Yogyakarta - Sirodjudin, Rizky Fazren; Kirana, Azra Kusuma Chandra; Subiyanto, Didik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to describe the influence of competence, servant leadership, and work discipline on employee performance. This research is classified as quantitative research. Data collection method uses a questionnaire, while data analysis technique uses multiple regression analysis and classic assumption tests consisting of normality test, multicollinearity test, and heteroskedasticity test. The analysis results show that (1) competence has a positive effect on employee performance with a significance value of 0.001 < 0.050, meaning the greater the competence, the better the employee performance. (2) servant leadership has a positive effect on employee performance with a significance value of 0.018 < 0.050, meaning the better the perception of leadership, the better the employee performance. (3) work discipline has a positive effect on employee performance with a significance value of 0.029 < 0.050, meaning the better the work discipline, the better the employee performance. (4) competence, servant leadership, and work discipline together have an influence on employee performance with a calculated Fvalue of 34.019 and a significance value of 0.000 < 0.05, meaning the better the competence, servant leadership, and work discipline, the better the employee performance.